2005
DOI: 10.1159/000086684
|View full text |Cite
|
Sign up to set email alerts
|

Association between Neopterin and Carotid Intima-Media Thickness in Hemodialysis Patients

Abstract: Background: Atherosclerotic lesions are heavily infiltrated by macrophages. Neopterin can be used as a marker of the activity of macrophages. Serum neopterin levels were elevated in non-renal patients with atherosclerosis. The intima-media thickness (IMT) of the carotid arteries in hemodialysis patients was significantly higher than in control subjects. In this study, we measured serum neopterin levels in hemodialysis patients and evaluated a possible correlation between neopterin levels and carotid IMT. Patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…Carotid arterial changes can reflect the progression of systemic atherosclerosis in asymptomatic general population. Erten et al 20 reported a significant positive correlation between serum NP levels and carotid intima media thickness (IMT) in hemodialysis patients. They suggested that NP could be associated with the severity of carotid atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Carotid arterial changes can reflect the progression of systemic atherosclerosis in asymptomatic general population. Erten et al 20 reported a significant positive correlation between serum NP levels and carotid intima media thickness (IMT) in hemodialysis patients. They suggested that NP could be associated with the severity of carotid atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Atherosclerosis seems to be more common in individuals with CKD (111) and ESRD (112)(113)(114)(115)(116). The atherosclerotic lesions in ESRD have a distinct morphology, with a more calcified appearance (as opposed to fibroatheromatous) and relatively increased medial thickness (as opposed to intimal) as compared with the general population (117).…”
Section: Pathophysiology Of Cvd In Ckdmentioning
confidence: 99%
“…Study by Malatino et al [3 ]showed that arterial systolic pressure, smoking and serum albumin were independent factors associated with carotid atherosclerosis in chronic dialysis patients. In hemodialysis patients, inflammation as denoted by C-reactive protein (CRP), interleukin-6, neopterin or hepatocyte growth factor [4,5,6,7] has been associated with carotid atherosclerosis. Carotid atherosclerosis in hemodialysis patients has also been described to be associated with hyperhomocysteinemia [8].…”
Section: Introductionmentioning
confidence: 99%